Analysis of high-dose intravenous immunoglobulin therapy in 16 patients with refractory autoimmune blistering skin disease: high efficacy and no serious adverse events - Seidling, Vera; Hoffmann, Jochen; Enk, Alexander; Hadaschik, Eva (Acta dermato-venereologica, 2013)
High-dose intravenous immunoglobulin (IVIG) therapy is used in patients with severe autoimmune blistering diseases that are refractory to standard immunosuppressive therapy. To determine the efficacy and frequency of adverse events of WIG therapy, we retrospectively analysed data for 16 patients with pemphigus vulgaris, pemphigus foliaceus, paraneoplastic pemphigus, bullous pemphigoid and paraneoplastic bullous pemphigoid. Frequency of adverse reactions and efficacy of IVIG were analysed over time with a scoring system for every 6 months of WIG therapy. Headache (43.8%) and fatigue (43.8%) were the most common side-effects recorded; serious adverse reactions did not occur. There was good overall efficacy, as measured by clinical response rates using a clinical score, as well as indicated by a mean reduction of 75.8% in the starting steroid dose.
Epub ahead of print Oct 16, 2012
Gesehen am 29.06.2018